1992
DOI: 10.1016/0167-7187(92)90046-2
|View full text |Cite
|
Sign up to set email alerts
|

The degree of spillovers and the number of rivals for maximum effective R &D

Abstract: The amount of cost-reduction or effective R&D that results in a symmetric sequential Nash equilibrium with quadratic payoffs and differentiated goods, is shown to increase with spillovers in "small group" industries and to achieve a maximum for spillovers that are not perfect in "large group" industries. Similar tendencies apply for consumer surplus, profits and static welfare. More rivals typically lead to reduced investments, output and profitability, while consumer surplus and welfare increase, or at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 138 publications
(60 citation statements)
references
References 14 publications
5
54
0
1
Order By: Relevance
“…Collaborative relationships with research organizations, in particular, can be even more beneficial compared to those with other kinds of external organizations due to a larger incoming spillover of new and specialized knowledge [61][62][63]. Our finding corroborates prior studies, which have suggested the importance of broader collaboration for system redesign and technological innovation for sustainable management [4].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Collaborative relationships with research organizations, in particular, can be even more beneficial compared to those with other kinds of external organizations due to a larger incoming spillover of new and specialized knowledge [61][62][63]. Our finding corroborates prior studies, which have suggested the importance of broader collaboration for system redesign and technological innovation for sustainable management [4].…”
Section: Discussionsupporting
confidence: 83%
“…Collaboration with research organizations, in particular, has been associated with more incoming spillover of R&D knowledge into the firm and less outgoing spillovers [61][62][63]. When firms collaborate with suppliers or competitors, they make an effort to maximize the gain of incoming spillovers as well as to minimize the loss of outgoing spillovers [64].…”
Section: The Effect Of Collaboration With Research Organizations On Ementioning
confidence: 99%
“…6 When goods are substitutes the level of product differentiation and the number of rivals are important parameters that determine the critical spillover level. (see De Bondt et al (1992), Röller et al (1997)). …”
Section: Industrial Organization Results On Randd Cooperation and Spillmentioning
confidence: 99%
“…between competing firms, stressing the importance of the degree of product market competition. When firms are not direct competitors but market independent or complementary goods, cooperation is associated with higher R&D investment levels independent of any critical level of spillovers (De Bondt et al, 1992;Röller et al, 1997). In such a setting where firms are less direct competitors, joint R&D and possible cheating have no detrimental effect in terms of strengthening the product market position of the rival.…”
Section: Theoretical Modelsmentioning
confidence: 99%